O gerenciamento de resíduos de construção e demolição em obras da Universidade Federal do Espírito Santo - Calente, Rodrigo de Souza (2017)
This dissertation approaches concepts related to sustainability in buildings, especially those carried out at the Universidade Federal do Espírito Santo, focusing on the management of construction and demolition waste, and discusses the importance of adopting ecologically correct procedures in the waste management. For that, an exploratory research was carried out, with a qualitative approach, of an applied nature. The procedures used were the bibliographical research, documentary research and case study, interviews and conversations with the staff of the Prefeitura Universitária, seeking to understand the management process of the Waste Construction held at the university. The need for a paradigm shift was emphasized in order to find solutions to the problem of building rubble, whether due to the scarcity of non-renewable natural resources or the lack of adequate space for deposition; either because of the high cost that this operation generates or because of the environmental and social problems caused. The benefits and impacts of waste management from the social and economic points of view were addressed. Finally, we report the current situation of the Federal University of Espírito Santo regarding the management of waste from buildings, the procedures that are adopted and some difficulties encountered for the implementation of sustainable management guidelines. It was hoped to identify possibilities of applying these concepts to the reality of the university, taking into account costs, term, safety and quality in its application. With the data collected, at the end of the work, an action plan was presented, containing alternatives of better procedures for the problem raised